286 PERCEPTIONS OF RESEARCH AMONGST OLDER ADULTS. (25th October 2022) - Davey, N; Connolly, E; McFeely, A; Bambrick, P; Pope, G; Mulcahy, R; Cooke, J; O'Regan, N
Abstract: Background: Older adults are often excluded from healthcare research, particularly those with cognitive impairment. It is crucial that study participants have given informed consent and partake in research of their own free will. People with cognitive impairment are not always able to engage in the informed consent process. This can lead to under-representation of this cohort in studies. Understanding older people's perceptions of research is important to better design policies and research studies that are inclusive of older adults. This pilot study aimed to gain a better understanding of older adults' views about healthcare research and what they imagine their wishes would be if they were unable to consent themselves due to memory problems. Methods: In this prospective observational study, participants were recruited from outpatient clinics. Consenting participants were surveyed over the phone to ascertain their perceptions of healthcare research. Results: Twenty-five interviews were conducted. Median age was 76.24 years (range 68-85 years). Most respondents reached at least second level education (80%), and most volunteered knowing very little about healthcare research. All participants had a nominated next of kin. Of 23 participants who had not previously been involved in healthcare research, none had been asked to do so. Most participants would be interested or very interested in participating in research if the study involved either survey questions (64%), chart review (88%), or additional investigations (68%), however only a minority were interested or very interested in partaking in research involving a trial drug (16%). Most participants (88%) would be happy or very happy for their next of kin to 'consent' on their behalf (if they themselves were unable to do so). Conclusion: In this study, older adults had clear views about healthcare research and a keenness to participate. This group of older adults expressed trust in their next of kin to make decisions on their behalf regarding research participation. More research is required to explore this area further.